Allocation of Treatment Responsibility in Adolescents With Epilepsy: Associations With Cognitive Skills and Medication Adherence. (13th February 2018) - Holbein, Christina E; Smith, Aimee W; Peugh, James; Modi, Avani C
Abstract: Objectives: To describe allocation of treatment responsibility (ATR) in adolescents with epilepsy, investigate associations between cognitive skills and ATR, and examine whether ATR for antiepileptic drugs (AEDs) predicted electronically monitored adherence. Method: Sixty adolescents with epilepsy and their caregivers completed the Allocation of Treatment Responsibility Scale and a battery of self-report measures. Medical chart review data and electronically monitored AED adherence were collected for 1 year. Descriptive data assessed ATR for caregivers and adolescents; multivariate hierarchical regressions tested associations between variables. Results: ATR for labs and clinic appointments was greatest for caregivers, while ATR for AEDs was more likely to be shared between caregiver and adolescent. Poorer attention was associated with greater caregiver responsibility for AEDs. Greater caregiver responsibility for AEDs was associated with higher electronically monitored adherence over 12 months. Conclusions: In adolescents with epilepsy, caregivers are responsible for most treatment tasks, although responsibility for taking medication was shared with the adolescent. Greater caregiver responsibility for medication results in better long-term AED adherence. ATR is an important construct that warrants further attention in research and clinical practice, especially in the context of transition and health outcomes in pediatric epilepsy.